2017
DOI: 10.1038/s41598-017-10278-1
|View full text |Cite
|
Sign up to set email alerts
|

Epicutaneous allergen application preferentially boosts specific T cell responses in sensitized patients

Abstract: The effects of epicutaneous allergen administration on systemic immune responses in allergic and non-allergic individuals has not been investigated with defined allergen molecules. We studied the effects of epicutaneous administration of rBet v 1 and rBet v 1 fragments on systemic immune responses in allergic and non-allergic subjects. We conducted a clinical trial in which rBet v 1 and two hypoallergenic rBet v 1 fragments were applied epicutaneously by atopy patch testing (APT) to 15 birch pollen (bp) allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Among the conventional AIT delivery options (subcutaneous or sublingual), we compared TDIT only with SCIT in this study. A recent study of epicutaneous immunotherapy (EPIT) reported advantages compared with SLIT 22 . To demonstrate the merits of TDIT, a comparative study with SLIT is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Among the conventional AIT delivery options (subcutaneous or sublingual), we compared TDIT only with SCIT in this study. A recent study of epicutaneous immunotherapy (EPIT) reported advantages compared with SLIT 22 . To demonstrate the merits of TDIT, a comparative study with SLIT is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of G‐CSF, GM‐CSF, IFN‐gamma, IL‐1 beta, IL‐2, IL‐4, IL‐5, IL‐6, IL‐7, IL‐8, IL‐10, IL‐12 (p70), IL‐13, IL‐17, MCP‐1, MIP‐1beta, and TNF‐alpha were measured in supernatants of 7 day PBMC cultures by Luminex multiplex assay (Bio‐Plex Pro™ Human Cytokine 17‐plex Assay; Bio‐Rad) according to the manufacturer's instructions as described . The Bio‐Plex ® 200 System (Bio‐Rad) was used for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Bound IgE was detected as described [ 25 ]. IgG 4 antibody levels specific for rApi m 1 and rVes v 5 were measured in 1:40 diluted serum samples by ELISA as described [ 26 ]. IgE(kU A /L)/IgG 4 (OD) ratios for Ves v 5 were calculated as described [ 27 ].…”
Section: Methodsmentioning
confidence: 99%